Synthesis and properties of photocross-linked poly(propylene fumarate)scaffolds - Fisher, J.P.; Holland, T.A.; Dean, D.; Engel, P.S.; Mikos, A.G.
The photocross-linking of poly(propylene fumarate)(PPF)to form porous scaffolds for bone tissue engineering applications was investigated. PPF was cross-linked using the photoinitiator bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (BAPO)and exposure to 30 min of long wavelength ultraviolet (UV)light. The porous photocross-linked PPF scaffolds (6.5 mm diameter cylinders)were synthesized by including a NaCl porogen (70, 80, and 90 wt
Keywords: TISSUE ENGINEERING SCAFFOLD; BIODEGRADABLE POLYMER; PHOTOCROSS-LINKING